Role of cytotoxic T cells and PD-1 immune checkpoint pathway in papillary thyroid carcinoma - Banerjee, Sohini; Nahar, Uma; Dahiya, Divya; Mukherjee, Soham; Dey, Pranab; Gupta, Rijuneeta; Radotra, Bishan; Sachdeva, Naresh; Sood, Ashwani; Bhadada, Sanjay Kumar; Bhansali, Anil (Frontiers in Endocrinology, 2022)
Background: Lymphocytic thyroiditis (LT) is frequently seen in tumour micro environment (TME) of papillary thyroid carcinomas (PTC). However, the character of these tumor infiltrating lymphocytes (TILs) is not well understood. Objective: We aim to define the TME of PTC cases by characterizing the TILs Design: Cross sectional observational study Patients: We enrolled 29 PTC (23 having concurrent LT), 14 LT and 13 hyperplastic nodules with LT (HN) patients from January 2016 to December 2020 Measurements: Immunohistochemical (IHC) expression of CD8, FoxP3, PD1 and PDL-1 was studied in PTC with LT and compared with HN. PD-1 and PDL-1 expression was correlated at mRNA level by quantitative Real Time PCR. Immunophenotyping of TILs was done in FNAC samples of PTC and LT by flow cytometry. Results: IHC revealed presence of CD8+ CTL (cytotoxic T lymphocytes) and FoxP3+ Treg (T regulatory cells) in 83% and 52% PTC with LT cases; respectively. Flowcytometric analysis of PTC samples revealed significant abundance of CTL compared to Treg, and higher CTL with lower Treg counts compared to LT. On IHC PD-1 positivity was noted in 56.5% PTC with LT cases; while, intermediate PDL-1 positivity in 70% cases. There was significant up regulation of PD-1 mRNA in PTC with LT. Significant correlation was noted with PDL-1 expression with lymph node metastasis and presence of Treg cells. Conclusions: Increased expression of PD-1 and PDL-1 in TME of PTC may provide a potential molecular mechanism for tumor survival despite predominance of CTLs, possibly through their inactivation or exhaustion.